Measurement of Atmospheric Neutrino Oscillations with Very Large Volume Neutrino Telescopes - J. P. Yáñez; A. Kouchner (Advances in High Energy Physics)
Neutrino oscillations have been probed during the last few decades using multiple neutrino sources and experimental set-ups. In the recent years, very large volume neutrino telescopes have started contributing to the field. First ANTARES and then IceCube have relied on large and sparsely instrumented volumes to observe atmospheric neutrinos for combinations of baselines and energies inaccessible to other experiments. Using this advantage, the latest result from IceCube starts approaching the precision of other established technologies and is paving the way for future detectors, such as ORCA and PINGU. These new projects seek to provide better measurements of neutrino oscillation parameters and eventually determine the neutrino mass ordering. The results from running experiments and the potential from proposed projects are discussed in this review, emphasizing the experimental challenges involved in the measurements.